A expansão da fronteira agrícola para o município de Correntina (BA): as (re)existências nas comunidades de Fecho de Pasto - Machado, Juliano Alfredo Crisóstomo (2022)
From the innovations caused by the Green Revolution, in general, the West region of Bahia began to be inserted in the logic of global production and the municipality of Correntina presents specificities in the set of transformations caused by capitalist expansion in the agrarian space. These transformations are reflected by different territorial actors. The dissertation presented here aims to analyze the production of agrarian space, identifying the actors responsible for the different forms of appropriation of this space. In this sense, the main objective is to highlight the position of territorial actors in the board of the agrarian space in Correntina (BA). For this, we will characterize and understand the performance of territorial actors in the regional context (West Bahia); understand the different capitalist and traditional perspectives present in the municipality, highlighting the (re)existence strategies of traditional pasture closing/Fundo e Fecho de Pasto communities. The theoric contribution used was based on a bibliographic review in books, theses, dissertations, monographs and texts published in journals; survey of secondary data to collect information on the subject from renowned agencies and institutions. In addition to the field work, made difficult by the COVID-19 pandemic, an analysis was carried out of the participation and publications of subjects linked to the pasture closure communities. From these methodological strategies, what can be seen is that actions of the State and Capital, in Correntina (BA), provoke the expropriation or threaten the traditional communities of pasture closing, the main strategy is the /grilagem land grabbing – which is renewed with the time – having violence as a conductor. And beyond that to making legislation more flexible, the State, through the responsible agencies for the titling of traditional territories, drags and hampers the process, wasting time and resources for the effective appropriation by the capital's representatives. However, the subjects of the communities find new strategies to remain on the land, adapting and thus building a (Re)existence. To avoid the conflicts, the territories of Fechos de Pasto de Correntina (BA) must be titled and the companies directly or indirectly responsible must be punished and inspected.